Escape from Mr. Lemoncello's library - Grabenstein, Chris (Yearling, 2014)
A group of kids are excited to spend a fun night at a lock-in at Mr. Lemoncello's newly opened library. However, the event is quite literal--now they will have to band together to find a way out before it is too late.